Miaphysitism in the Perspective of Ecumenism: Reinterpretation of St. Cyril of Alexandria’s Christology - Zemin, Tan (International Journal of Sino-Western Studies, 2022)
Miaphysitism, originating from the well-known phrase used by St Cyril of Alexandria, mia physis (or mia hypostasis) tou Theou logou searkomene, is most basic, central, and important conversations in the dialogue between the Oriental Churches, that is Non-Chalcedon Churches, and Chalcedon Churches under the Ecumenical Movement, and is the theological basis for theological reconciliation and reunification of the two sides after more than ten centuries of separation since the Council of Chalcedon. After investigating the meaning and usage of the key words “physis” and “hypostasis”, this article will analyze the basic connotations of mia physis (natural union) and mia hypostasis(hypostatic union) in detail, as well as the connection and distinction between them, and explore the reason of the theological reconciliation and reunification between the Oriental Churches and Chalcedon Churches. In the last part, this article will try to discuss the significance of Miaphysitism to Construction of Chinese theology.